‘Trust in the Lord’: Hezekiah, Kings and Isaiah - Olley, John W. (Tyndale bulletin, 1999)
The Hezekiah narrative (2 Kings 18-20 // Isaiah 36-39) is unique in the Former Prophets in its repeated use of בָטַח trust, rely on’. An exploration of the context and content of חַטָּב in the narrative and elsewhere in Isaiah, Psalms, Proverbs and other prophetic literature points to a consistent pattern of true and false grounds for ‘trust’. In particular there is no basis in the ‘inviolability of Zion’. The drama of the narrative is sharper in the context of Isaiah and may have been shaped soon after Sennacherib’s death, with possible wisdom influence. At the same time, the redactor of Kings has seen ‘trust’ as a key feature in Hezekiah’s reign. The relevance of the narrative to readers of the canonical Kings and Isaiah is also considered. There is significance for all in the worship of YHWH alone together with humble obedience. It is his honour that is affirmed among the nations.